Influence of Perfluorinated End Groups on the SFRD of [Pt(cod)Me(CnF2n+1)] onto Porous Al2O3 in CO2 under Reductive Conditions1. Issue 38 (5th August 2013) - Aggarwal, Vikas; Reichenbach, Linus F.; Enders, Mirja; Muller, Thierry; Wolff, Simone; Crone, Marlene; Türk, Michael; Bräse, Stefan
Abstract The optimized synthesis of a range of cyclooctadiene‐stabilized Pt complexes that contained different perfluoro‐alkane chains, [Pt(cod)Me(CnF2n+1)], is presented. These metal–organic compounds were employed in the so‐called supercritical fluid reactive deposition (SFRD) in CO2 under reductive conditions to generate metallic nanoparticles on aluminum oxide as a porous support. Thus, Al2O3‐supported Pt nanoparticles with a narrow particle‐size distribution were obtained. At a reduction pressure of 15.5 MPa and a temperature of 353 K, particle diameters of d50=2.3–2.8 nm were generated. Decreasing the pressure during the reduction reaction led to slightly larger particles whilst decreasing the amount of organometallic precursor in CO2 yielded a decrease in the particle size from x50=3.2 nm to 2.6 nm and a particle‐size distribution of 2.2 nm. Furthermore, substitution of the CH3 end group by the CnF2n+1 end groups led to a significant drop in Pt loading of about 50 %. Within the series of perfluorinated end groups that were considered, the Pt complex that contained a branched perfluoro‐isopropyl group showed the most‐interesting results when compared to the control precursor, [Pt(cod)Me2] (1).